Specific peroxidases differentiate Brachypodium distachyon accessions and are associated with drought tolerance traits - Luo, Na (Ann Bot, 2016)
Background and Aims Brachypodium distachyon (Brachypodium) is a model system for studying cereal, bioenergy, forage and turf grasses. The genetic and evolutionary basis of the adaptation of this wild grass species to drought stress is largely unknown. Peroxidase (POD) may play a role in plant drought tolerance, but whether the allelic variations of genes encoding the specific POD isoenzymes are associated with plant response to drought stress is not well understood. The objectives of this study were to examine natural variation of POD isoenzyme patterns, to identify nucleotide diversity of POD genes and to relate the allelic variation of genes to drought tolerance traits of diverse Brachypodium accessions. Methods Whole-plant drought tolerance and POD activity were examined in contrasting ecotypes. Non-denaturing PAGE and liquid chromatography–mass spectrometry were performed to detect distinct isozymes of POD in 34 accessions. Single nucleotide polymorphisms (SNPs) were identified by comparing DNA sequences of these accessions. Associations of POD genes encoding specific POD isoenzymes with drought tolerance traits were analysed using TASSEL software. Key Results Variations of POD isoenzymes were found among accessions with contrasting drought tolerance, while the most tolerant and susceptible accessions each had their own unique POD isoenzyme band. Eight POD genes were identified and a total of 90 SNPs were found among these genes across 34 accessions. After controlling population structure, significant associations of Bradi3g41340.1 and Bradi1g26870.1 with leaf water content or leaf wilting were identified. Conclusions Brachypodium ecotypes have distinct specific POD isozymes. This may contribute to natural variations of drought tolerance of this species. The role of specific POD genes in differentiating Brachypodium accessions with contrasting drought tolerance could be associated with the general fitness of Brachypodium during evolution.